Women at work women on a "balance beam" - the case of selected women workers in San Pascual, Batangas Province, Philippines - Pacardo-Mercado, Athenee B. (2013)
The study centers on the social dynamics happening at home which continues to alter the traditional division of labor. Specifically, it revolves on the range of adjustments women undertake to resolve emerging issues at home brought about by their participation in paid employment. Today, as women continue to struggle in performing their multiple roles brought about by both reproductive and productive work, they constantly experience tensions and stress. Nevertheless, despite the given conditions, women continue to exercise resiliency as they constantly stretch their inner resources to be able to meet to the demands of both reproductive and productive work. However, women's participation in paid work becomes their foundation in slowly exercising their inner power. They are now able to liberate themselves through the process of negotiation, where they feel capable to resist husbands' persistent demands at home. As women continue to assert themselves, they are now able to shift their position in the power structure of the family, from being traditionally inferior and subordinate to becoming more confident and independent individuals. But even with their increasing self-esteem and feeling of independence from their husbands, the narratives show that women constantly live in an unending cycle of "balancing" their multiple roles to maintain and sustain peace and harmony in the family. Women have formed an internalized "balance beam" as they constantly juggle their own personal development while living within a cultural expectations, norms and values. The balancing acts of women have become their means to liberate themselves from the bondage of patriarchy.
Keywords: Working women